2002
DOI: 10.1034/j.1600-0536.2002.460604.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational dermatoses among fibreglass‐reinforced plastics factory workers

Abstract: Fibreglass-reinforced plastics (FRP) factory workers are at high risk of developing occupational dermatoses because of their exposure to many chemicals used in the manufacture of plastics as well as to glass fibre or dust. Patch tests were carried out on 29 workers involved in FRP manufacturing processes where unsaturated polyester (UP) resin was used, to investigate the causes of their skin problems. Of the 22 workers who reported experiencing skin problems, 16 showed positive results to at least 1 chemical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Exposure may also damage peripheral nerves and cause changes to the kidneys and blood. Numerous studies have shown that styrene exposures were linked to central and peripheral neurologic, 3,4,5 optic, 6,7 and irritant 8 effects when occupational exposures to styrene vapors in air were measured at concentrations greater than 50 parts per million (ppm). There is also evidence concerning the influence of occupational styrene exposure on sensory nerve conduction indicating that: (1) 5% to 10% reductions can occur after exposure at 100 ppm or more; (2) reduced peripheral nerve conduction velocity and sensory amplitude can occur after styrene exposure at 50 to 100 ppm; (3) slowed reaction time appears to begin after exposures as low as 50 ppm; and, (4) statistically significant loss of color discrimination (dyschromatopsia) may occur.…”
Section: Exposure Hazards Of Styrenementioning
confidence: 99%
“…Exposure may also damage peripheral nerves and cause changes to the kidneys and blood. Numerous studies have shown that styrene exposures were linked to central and peripheral neurologic, 3,4,5 optic, 6,7 and irritant 8 effects when occupational exposures to styrene vapors in air were measured at concentrations greater than 50 parts per million (ppm). There is also evidence concerning the influence of occupational styrene exposure on sensory nerve conduction indicating that: (1) 5% to 10% reductions can occur after exposure at 100 ppm or more; (2) reduced peripheral nerve conduction velocity and sensory amplitude can occur after styrene exposure at 50 to 100 ppm; (3) slowed reaction time appears to begin after exposures as low as 50 ppm; and, (4) statistically significant loss of color discrimination (dyschromatopsia) may occur.…”
Section: Exposure Hazards Of Styrenementioning
confidence: 99%
“…Exposure may also damage peripheral nerves and cause changes to the kidneys and blood. Numerous studies have shown that styrene exposures were linked to central and peripheral neurologic, 4, , 5 6 optic, 7,8 and irritant 9 effects when occupational exposures to styrene vapors in air were measured at concentrations greater than 50 parts per million (ppm). There is also evidence concerning the influence of occupational styrene exposure on sensory nerve conduction indicating that: (1) 5% to 10% reductions can occur after exposure at 100 ppm or more; (2) reduced peripheral nerve conduction velocity and sensory amplitude can occur after styrene exposure at 50 to 100 ppm; (3) slowed reaction time appears to begin after exposures as low as 50 ppm; and, (4) statistically significant loss of color discrimination (dyschromatopsia) may occur.…”
Section: Exposure Hazards Of Styrenementioning
confidence: 99%
“…Another study of occupational dermatoses among fiberglassreinforced plastics factory workers asserted that these workers are at high risk of developing occupational dermatoses because of their exposure to many chemicals used in the manufacture of plastics as well as to fiberglass or dust. 15 Some of these chemicals are UP base resin, cobalt chloride, benzoyl peroxide, methyl ethyl ketone peroxide, para-tertiary butyl catechol, styrene, and formaldehyde. Of the 29 workers in the study who underwent patch testing for the chemicals listed above, 62.1% were sensitized to at least one chemical.…”
Section: Medicalmentioning
confidence: 99%
“…Of the 29 workers in the study who underwent patch testing for the chemicals listed above, 62.1% were sensitized to at least one chemical. 15 Based on the results of the survey at DCM, skin irritation experienced by workers is likely caused by chemical exposure as well as fiberglass or dust. In any case, direct exposure to fiberglass and chemicals should be avoided.…”
Section: Medicalmentioning
confidence: 99%